Character matters : shepherding in the fruit of the spirit - Menikoff, Aaron (Chicago : Moody Publishers, 2020)
"Pastor, it's time to turn down the noise and focus on what matters. Today's pastoral world is packed with books, conferences, and seminars teaching you different techniques for being an all-star pastor, growing your church quickly, and changing the world one step at a time. But the key to true success is much harder and much simpler. Pastors are called to be faithful, to have exemplary character, and to love Jesus-without these things their ministry ends up harming others rather than helping them. Character Matters was designed to help you slow down, cut through the noise and distractions, and focus on what matters-the Fruit of the Spirit. Each chapter is a guided meditation on one aspect of the fruit of the Spirit. As you reflect and spend time focusing on the simple things that matter, you'll see your heart and ministry changed, slowly, surely, and by the power of the Spirit"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Clergy -- Religious life; Fruit of the Spirit -- Meditations; Spiritual formation; Character -- Religious aspects -- Christianity; Pastoral theology